2017 IEEE International Conference on Fuzzy Systems (FUZZ-IEEE) 2017
DOI: 10.1109/fuzz-ieee.2017.8015459
|View full text |Cite
|
Sign up to set email alerts
|

Cross product kernels for fuzzy set similarity

Abstract: We present a new kernel on fuzzy sets: the cross product kernel on fuzzy sets which can be used to estimate similarity measures between fuzzy sets with a geometrical interpretation in terms of inner products. We show that this kernel is a particular case of the convolution kernel and it generalizes the widely-know kernel on sets towards the space of fuzzy sets. Moreover, we show that the cross product kernel on fuzzy sets performs an embedding of probability measures into a reproduction kernel Hilbert space. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Incorporating non-vectorial fuzzy data into a normed vectorial space such as kernel Hilbert space (RKHS) has given birth to some innovating methods [40,41], which use a positive definite kernel function specified on fuzzy sets. The kernel proposed in [42] measures the resemblance between fuzzy sets in RKHS. It has been demonstrated in this approach that such a kernel is a special case of the convolution kernel.…”
Section: Positive-definite Kernel Functions On Fuzzy Setsmentioning
confidence: 99%
“…Incorporating non-vectorial fuzzy data into a normed vectorial space such as kernel Hilbert space (RKHS) has given birth to some innovating methods [40,41], which use a positive definite kernel function specified on fuzzy sets. The kernel proposed in [42] measures the resemblance between fuzzy sets in RKHS. It has been demonstrated in this approach that such a kernel is a special case of the convolution kernel.…”
Section: Positive-definite Kernel Functions On Fuzzy Setsmentioning
confidence: 99%
“…The cross product kernel on fuzzy sets was presented by Guevara et al [2017]. That kernel always would be positive definite if k 1 and k 2 are positive definite.…”
Section: Kernelsmentioning
confidence: 99%
“…It can be shown that k × is indeed a kind of convolution kernel (Haussler [1999]), and that under some assumptions it embeds probability distributions into RKHS. This kernel was successfully used in supervised classification on attribute noisy datasets, where it was shown that the kernel is resistant to injected random noise over the values of the predictors (see reference Guevara et al [2017] for the experiments).…”
Section: Kernelsmentioning
confidence: 99%
“…Kernel functions have been designed for strings [Watkins, 1999, Lodhi et al, 2002 or more generally for sequences [Király and Oberhauser, 2019], sets [Haussler, 1999, Gärtner et al, 2002, rankings [Jiao and Vert, 2016], fuzzy domains [Guevara et al, 2017] and graphs [Borgwardt et al, 2020], which renders them broadly applicable. Their extension to the space of probability measures [Berlinet andThomas-Agnan, 2004, Smola et al, 2007] allows to represent distributions in a reproducing kernel Hilbert space (RKHS) by the so-called mean embedding.…”
Section: Introductionmentioning
confidence: 99%